2020
DOI: 10.1093/geront/gnaa220
|View full text |Cite
|
Sign up to set email alerts
|

Findings of Sequential Pilot Trials of Aliviado Dementia Care to Inform an Embedded Pragmatic Clinical Trial

Abstract: Background and Objectives Many investigators of Alzheimer’s disease and related dementias (AD/ADRD) are unfamiliar with the embedded pragmatic clinical trials (ePCTs) and the indispensable pilot phase preceding ePCTs. This paper provides a much-needed example for such a pilot phase and discusses implementation barriers and additional infrastructure and implementation strategies developed in preparation for a nationwide AD/ADRD ePCT. Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 32 publications
0
31
0
Order By: Relevance
“…There are a variety of innovations aiming to improve end‐of‐life care for PWD. Programs like Aliviado Health aim to improve dementia expertise of clinicians within hospice, home health, and long‐term care models 34–36 . The UCLA Alzheimer's & Dementia Care co‐management program shows positive end‐of‐life outcomes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…There are a variety of innovations aiming to improve end‐of‐life care for PWD. Programs like Aliviado Health aim to improve dementia expertise of clinicians within hospice, home health, and long‐term care models 34–36 . The UCLA Alzheimer's & Dementia Care co‐management program shows positive end‐of‐life outcomes 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Participants were recruited from an IDT undergoing a quality improvement program, Aliviado Dementia Care-Hospice Edition, in the complexities of providing dementia care in the hospice setting. 31 Methodology from this study are reported in greater detail elsewhere. 31 Participants were invited to complete the survey after completion of the dementia care training of the Aliviado program.…”
Section: Instrumentsmentioning
confidence: 99%
“…31 Methodology from this study are reported in greater detail elsewhere. 31 Participants were invited to complete the survey after completion of the dementia care training of the Aliviado program. All data was collected between March and September 2019.…”
Section: Instrumentsmentioning
confidence: 99%
“…In order to properly address these issues, we believe that the clinical research apparatus requires a new priority: embedded pragmatic clinical trials [ 57 ]. These studies, which are integrated into standard medical care using routinely collected clinical information, generate real-world evidence without the limitations associated with observational studies or the time, expense, and lack of generalizability that are barriers to conducting conventional randomized clinical trials [ 58–60 ].…”
Section: Expert Opinionmentioning
confidence: 99%